Satellite observed cloud distribution over the Indian Ocean during the southwest monsoon season - PRASAD, ONKARI; MISRA, D. K.; JAIN, R. K. (MAUSAM, 1983)
The cloud distribution over the Indian Ocean has been studied for the two consecutive southwest monsoon seasons of the years 1973 and 1974 with the help of cloud imagery received from NOAA-2 spacecraft in the visible and thermal infrared channels. The cloud distribution shows an interesting mean pattern and demarcates the position of Southern Hemispheric Equatorial Trough (SHET). Weak tropical disturbances which appear as amorphous convective cloud clusters are predominant in the near equatorial regions of the Indian Ocean in this season. The study reveals a negative association between the southwest monsoon activity over India and the intensity of SHET. During weak monsoon conditions over India there is intense convective activity over the Indian Ocean between equator and Lat. to Sin association with active SHET.